Influence of log temperature in irregularities on strand geometry detected by digital image analysis - Gaete-Martínez, Victor; M. Shaler, Stephen (Maderas. Ciencia y Tecnología, 2025)
Oriented Strand Board (OSB) wood strands, while often idealized as being rectangular and slender objects, are in fact typically very complex in shape. This complexity is important to the manufacture and performance of OSB as it influences forming, screening, blending, formation and ultimately performance of the panel. In a mill setting, strand geometry is defined by average length, width and thickness values as determined through simple caliper measurements and/or screen analyses (Gilson). The application of CCD cameras and digital image analysis techniques to rapidly acquire and analyze complex strand geometry will allow the processing of large amounts of data, thereby creating the potential for statistical process control applications. Aspen (Populus grandidentata) strands were produced from logs subjected to -6ºC (20F), 21ºC (70F) and 60ºC (140F). Grey scale digital images of individual strands were acquired using a CCD camera (1296 x 1016 pixels) under direct lighting. The complexity of strand geometry was characterized by a variety of automated measuring procedures. As a result of this research the feasibility of applying this methodology to study geometrical distributions in strands was established. Area, length and width presented changes in their distributions due to the effect of log temperature. It was found that the irregularity ratio of strands was variable and strongly influenced by log temperature at time of stranding as well as other geometries. Statistical correlation between strands irregularity and log temperature was found (p-value<0.001).